Effects of Rediset on the adhesion, stripping, thermal and surface morphologies of PG76 binder. (30th April 2020) - Rahmad, Suzielah; Izzi Md. Yusoff, Nur; Rosyidi, Sri Atmaja P.; Haji Badri, Khairiah; Widyatmoko, Iswandaru
Highlights: Effects of adhesion, stripping, surface morphologies and thermal behaviour of PG76-Rediset were investigated. The adhesion and stripping properties were improved by the anti-stripping agent in Rediset. Changes can be seen clearly by the shapes and distribution of the bees' structures. Thermal decomposition takes place at temperature between 300 and 500°C. Abstract: Apart from lowering the production and application temperature, Warm Mix Asphalt (WMA) additive has the potential to enhance the adhesion property of the base binders. Surface free energy (SFE) from contact angles was determined by sessile drop device (SDD) to find out the work of adhesion of WMA additive-modified binders. It is shown that addition of WMA additive at different weight percentage would initiate dissimilar implications on surface properties. Test data are compared with the nanoscale adhesion force of WMA additive-PG76 using atomic force microscopy (AFM). The connection between the contact angle analysis with the topography was also investigated; SFE and AFM results exhibit some agreement in findings. The WMA additive had improved the adhesion characteristics of warm mix additive-modified binders. In addition to that, adhesion and stripping behaviour of the blends were also observed via the Boiling Water test. The test demonstrated that the adhesive characteristics of the blending are at its best and the results inclined to the conclusion that the WMA additive had effect on the adhesion and stripping behaviour. The thermogravimetry analysis (TGA) was carried out to observe the thermal behaviour of the samples. It is found that the thermal decomposition of these blends takes place at temperature between 300 and 500 °C. Together, all the findings are in agreement that the addition of Rediset into PG76 could benefit for the WMA application.